Developmental changes within the extended face processing network: A cross‐sectional functional magnetic resonance imaging study. Issue 1 (10th November 2021) - Sahraei, Isabell; Hildesheim, Franziska E.; Thome, Ina; Kessler, Roman; Rusch, Kristin M.; Sommer, Jens; Kamp‐Becker, Inge; Stark, Rudolf; Jansen, Andreas
Abstract: In the field of face processing, the so‐called "core network" has been intensively researched. Its neural activity can be reliably detected in children and adults using functional magnetic resonance imaging (fMRI). However, the core network's counterpart, the so‐called "extended network, " has been less researched. In the present study, we compared children's and adults' brain activity in the extended system, in particular in the amygdala, the insula, and the inferior frontal gyrus (IFG). Using fMRI, we compared the brain activation pattern between children aged 7–9 years and adults during an emotional face processing task. On the one hand, children showed increased activity in the extended face processing system in relation to adults, particularly in the left amygdala, the right insula, and the left IFG. On the other hand, lateralization indices revealed a "leftward bias" in children's IFG compared to adults. These results suggest that brain activity associated with face processing is characterized by a developmental decrease in activity. They further show that the development is associated with a rightward migration of face‐related IFG activation, possibly due to the competition for neural space between several developing brain functions ("developmental competition hypothesis").